1992
DOI: 10.1063/1.462486
|View full text |Cite
|
Sign up to set email alerts
|

π-electron calculations of polarizabilities in conjugated systems

Abstract: Articles you may be interested in πelectron polarizabilities of infinite organic polymers J. Chem. Phys. 97, 9389 (1992); 10.1063/1.463315Ultraviolet photoemission study of oligothiophenes: The effect of irregularity on πelectron systems A screened potential molecularorbital calculation of the πelectron systems of metalloporphin, metallochlorin, and metallobacteriochlorin A screened potential molecularorbital calculation of the πelectron system of porphyrin Finite-field technique has been applied to the calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…13 The only change is relative to the parametrization of the bielectronic PPP integrals. The previous results obtained on long oligomers including topological defects (solitons, polarons, and bipolarons) have shown that the commonly used Ohno integrals (see, e.g., Ref.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…13 The only change is relative to the parametrization of the bielectronic PPP integrals. The previous results obtained on long oligomers including topological defects (solitons, polarons, and bipolarons) have shown that the commonly used Ohno integrals (see, e.g., Ref.…”
Section: Methodsmentioning
confidence: 99%
“…The polarizability per unit cell has been calculated for different values of this alternation and compared to results obtained on the same type of calculation on long 0ligomers. 13 The Fock matrix elements of an infinite system described by the Pariser-Parr-Pople approximations is…”
Section: (9)mentioning
confidence: 99%
See 2 more Smart Citations
“…A prominent class of materials displaying NLO absorption and concomitant generation of the OL effect is constituted by conjugated organic molecules [13] which are characterized by the presence of an extended network of loosely bound π-electrons with oxidation energies ranging within the approximate interval 6.5-8.5 eV [14]. The most relevant feature of the π-electrons is their high polarizability [15,16]. This allows a quasi-instantaneous response of the molecule to the perturbations induced by rapidly variable external electric fields and the interaction between light and conjugated molecule generally brings about low losses and scarce dispersion of the energy transported by the optical wave [5].…”
Section: Introductionmentioning
confidence: 99%